Diabetes insipidus after discontinuation of vasopressin infusion for septic shock. (11th September 2017) - Rana, H.; Ferguson, N.; Dicpinigaitis, P. V.
Summary: What is known and objective: Despite widespread use of vasopressin for the treatment of septic shock, few cases of diabetes insipidus (DI) following its discontinuation have been reported. Case summary: A 54‐year‐old man presented with pneumonia progressing to septic shock, requiring norepinephrine and vasopressin for refractory hypotension. After clinical improvement, the patient on 3 separate occasions developed polyuria and severe hypernatremia upon discontinuation of vasopressin, with prompt recovery upon its resumption. What is new and conclusion: Occurrence of DI upon discontinuation of vasopressin infusion appears to be rare, but incidence may be underestimated due to a paucity of published reports. Actual incidence and underlying mechanism of this phenomenon remain to be elucidated. Abstract : Occurrence of diabetes insipidus (DI) after cessation of vasopressin infusion for blood pressure support in a patient with septic shock. Note that on three occasions after discontinuation of vasopressin infusion, significant increase in serum sodium, and increase in urine output occurred, promptly reversed by re‐initiation of vasopressin infusion.